How can healthcare organizations implement patient-centered care? Examining a large-scale cultural transformation - Barbara G. Bokhour; Gemmae M. Fix; Nora M. Mueller; Anna M. Barker; Sherri L. Lavela; Jennifer N. Hill; Jeffrey L. Solomon; Carol VanDeusen Lukas (BMC, 2018)
Abstract Background Healthcare organizations increasingly are focused on providing care which is patient-centered rather than disease-focused. Yet little is known about how best to transform the culture of care in these organizations. We sought to understand key organizational factors for implementing patient-centered care cultural transformation through an examination of efforts in the US Department of Veterans Affairs. Methods We conducted multi-day site visits at four US Department of Veterans Affairs medical centers designated as leaders in providing patient-centered care. We conducted qualitative semi-structured interviews with 108 employees (22 senior leaders, 42 middle managers, 37 front-line providers and 7 staff). Transcripts of audio recordings were analyzed using a priori codes based on the Consolidated Framework for Implementation Research. We used constant comparison analysis to synthesize codes into meaningful domains. Results Sites described actions taken to foster patient-centered care in seven domains: 1) leadership; 2) patient and family engagement; 3) staff engagement; 4) focus on innovations; 5) alignment of staff roles and priorities; 6) organizational structures and processes; 7) environment of care. Within each domain, we identified multi-faceted strategies for implementing change. These included efforts by all levels of organizational leaders who modeled patient-centered care in their interactions and fostered willingness to try novel approaches to care amongst staff. Alignment and integration of patient centered care within the organization, particularly surrounding roles, priorities and bureaucratic rules, remained major challenges. Conclusions Transforming healthcare systems to focus on patient-centered care and better serve the "whole" patient is a complex endeavor. Efforts to transform healthcare culture require robust, multi-pronged efforts at all levels of the organization; leadership is only the beginning. Challenges remain for incorporating patient-centered approaches in the context of competing priorities and regulations. Through actions within each of the domains, organizations may begin to truly transform to patient-driven care.